Analysis of Wage Levels and Job Satisfaction on Employee Performance of PT. Adira Dinamika Multi Finance Tbk, in the City of Tebing Tinggi - Ben Setiawan Barus (Jurnal Mantik, 2022)
This study aims to determine the effect of Wage Levels and Job Satisfaction on Employee Performance. The effect that we want to know is whether there is an effect of each independent variable on the dependent variable. This type of research is explanatory research that explains the relationship between variables through hypothesis testing. This study uses a sample of 62 respondents who work as employees of PT. Adira Dinamika Multi Finance Tebing Tinggi City. This study uses quantitative research with the help of the IBM SPSS 25.00 application. The results of hypothesis testing use multiple linear regression analysis with one equation that makes Y the dependent variable and the conclusion shows that H1 is accepted, that is, there is a positive influence between the Wage Level variables (X1) on the Employee Performance variable (Y). This means that H1 in this study is accepted because there is a positive influence between the Wage Level variable (X1) on the Employee Performance Variable (Y) on the employees of PT. Adira Dinamika Multi Finance. H2 is also accepted, namely there is a positive influence between the variable job satisfaction (X2) on the employee performance variable (Y). This means that H2 in this study is accepted because there is a positive influence between the Job Satisfaction variable (X2) on the Employee Performance Variable (Y) on the employees of PT. Adira Dinamika Multi Finance. And H3 in this study is also accepted, which shows that the Wage Level (X1) and the Job Satisfaction variable (X2) simultaneously affect Employee Performance (Y). This means that H3 in this study is accepted because the Wage Level (X1) and the Job Satisfaction variable (X2) simultaneously affect Employee Performance (Y) on employees of PT. Adira Dinamika Multi Finance Tebing Tinggi City.